2021
DOI: 10.1097/mcc.0000000000000835
|View full text |Cite
|
Sign up to set email alerts
|

Interventional treatment of acute myocardial infarction-related cardiogenic shock

Abstract: Purpose of reviewAcute revascularization is with some evidence the only intervention proven to improve the prognosis in myocardial infarction-related cardiogenic shock but several interventions are continuously being investigated in order to increase survival among these patients. In this review, several aspects related to the interventional treatment of cardiogenic shock are discussed chronologically from symptom debut to leaving the cardiac catheterization laboratory.Recent findingsIn the randomized CULPRIT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…The pathological mechanism is the blockage of the microvascular lumen by platelets, leukocyte debris and microthrombi, edema of the endothelium, or compression by edema of the myocardial tissue, as well as the pathological inflammatory response, vasospasm due to thrombus, and vasoconstrictor secreted by the endothelium [ 13 ]. Persistent myocardial ischemia and massive necrosis due to no recurrent flow are important determinants of death and other adverse events after infarction [ 14 ]. However, in recent years, it has been found that prolonged microcirculatory impairment with severe tissue ischemia and hypoxia can lead to destruction of capillary walls and spillage of red blood cells from the vessels into the tissue interstitium, a more severe form of reperfusion injury [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathological mechanism is the blockage of the microvascular lumen by platelets, leukocyte debris and microthrombi, edema of the endothelium, or compression by edema of the myocardial tissue, as well as the pathological inflammatory response, vasospasm due to thrombus, and vasoconstrictor secreted by the endothelium [ 13 ]. Persistent myocardial ischemia and massive necrosis due to no recurrent flow are important determinants of death and other adverse events after infarction [ 14 ]. However, in recent years, it has been found that prolonged microcirculatory impairment with severe tissue ischemia and hypoxia can lead to destruction of capillary walls and spillage of red blood cells from the vessels into the tissue interstitium, a more severe form of reperfusion injury [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Persistent myocardial ischemia and massive necrosis due to no recurrent flow are important determinants of death and other adverse events after infarction [14]. However, in recent years, it has been found that prolonged microcirculatory impairment with severe tissue ischemia and hypoxia can lead to destruction of capillary walls and spillage of red blood cells from the vessels into the tissue interstitium, a more severe form of reperfusion injury [15].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, through bioinformatics, differential expression of mRNA of ICM functional annotation (GO and KEGG) pathway analysis, it was shown that there was significant enrichment in fibrosis and endoplasmic reticulum stress pathways, and that these pathways prompt the pathogenesis of ICM (33). In addition, we also constructed differentially expressed lncRNA-related Hub gene networks in ICM.…”
Section: Discussionmentioning
confidence: 98%
“…PCI is employed to recanalize stenosed or occluded coronary arteries, facilitating reperfusion of the ischemic myocardium and thereby improving cardiac function. It has become a primary clinical treatment for AMI [16]. However, post-PCI, a majority of patients experience psychological stress, leading to varying degrees of negative emotions.…”
Section: Discussionmentioning
confidence: 99%